Determination of Binary Gas Mixtures by Measuring the Resonance Frequency in a Piezoelectric Tube - Kanchalar Keeratirawee; Peter C. Hauser (My University, 2022)
The composition of gas mixtures may be determined via changes of the speed of sound. As this affects the resonance frequency of the gas inside a tube, indirect measurements through a frequency analysis are also possible. It is demonstrated that this may be carried out with unprecedented simplicity by the novel employment of a piezoelectric tube which serves at the same time as a resonance tube and as transducer into the electronic domain. Experiments were run using a simple diecast aluminum box as the measuring cell, inside which the piezoelectric tube made from lead zirconium titanate with 30-mm length and 5.35-mm inner diameter was suspended. A small loudspeaker placed into the cell served for excitation of the resonance. Peak frequencies between 3910 and 14,590 Hz (for pure CO2 and He, respectively) were obtained. Two component mixtures of O2/N2, CO2/N2, and He/N2 at various composition were tested. A linear frequency change from 4790 to 5100 Hz was observed when going from pure O2 to pure N2.
Keywords: Acoustic resonance; Lead zirconate titanate; Advanced MEMS and NEMS Technologies